The Effect of Low Volume Interval Training on Resting Blood Pressure in Pre-hypertensive Subjects: A Preliminary Study. Issue 2 (2nd April 2016) - Skutnik, Benjamin C.; Smith, Joshua R.; Johnson, Ariel M.; Kurti, Stephanie P.; Harms, Craig A.
ABSTRACT: Objectives : Clinically pre-hypertensive adults are at a greater risk of developing hypertension, stiffened arteries, and other cardiovascular risks. Endurance exercise training has been shown to improve elevated resting blood pressure and C-reactive protein (CRP) levels. However, a primary barrier preventing individuals from engaging in regular physical activity is a lack of time. The purpose of our study was to determine if a high-intensity interval training (HIIT) protocol would be as effective as continuous aerobic endurance training (ET) on resting blood pressure in pre-hypertensive participants. Additionally, this study investigated the effects of HIIT vs. ET on CRP. Methods : Twelve pre-hypertensive participants (33.3±6.1 yrs; 3M/9W) participated in 8 weeks of cycle ergometer exercise training. The ET exercised for 30 continuous min/day, 4 days/week at 40% reserve. The HIIT exercised at a 1:1 work-to-rest for 20 min/day, 3 days/week at 60% peak power. Resting mean arterial pressure and CRP were compared throughout the study. Results : Both groups showed decreases (p<0.001) in mean arterial pressure (ET: -11.5 ± 5.9 mmHg; HIIT: -8.6 ± 4.8 mmHg) following the 8 weeks. For CRP, there was a significant decrease (p=0.014) as a main effect of time. increased (p<0.001) approximately 25% for both HIIT and ET. Conclusion : These preliminary data suggest HIIT and ET similarly decreased resting blood pressure and increased .